2016
DOI: 10.1371/journal.pone.0161853
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Genetic Diversity of HIV-1 in Incident and Prevalent Infections among Malaysian Blood Donors: Multiple Introductions of HIV-1 Genotypes from Highly Prevalent Countries

Abstract: Transfusion-transmissible infections including HIV-1 continue to pose major risks for unsafe blood transfusions due to both window phase infections and divergent viruses that may not be detected by donor screening assays. Given the recent emergence of several HIV-1 circulating recombinant forms (CRFs) in high-risk populations in the Southeast Asia region, we investigated the genetic diversity of HIV-1 among the blood donors in Kuala Lumpur, Malaysia. A total of 211 HIV-positive plasma samples detected among 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The proportion of recent infections (within 130 days) among all newly diagnosed PLWH was only 2.73% in this area, which also deserves concern. The proportion of recent infections was lower than that in other areas with a high rate of HIV in China (40,41) and those in other countries (40,42), indicating that most of the newly diagnosed PLWH were not detected in time. HIV might be spread by many individuals unaware of their infection, leading to a widespread of HIV in this area.…”
Section: Discussionmentioning
confidence: 66%
“…The proportion of recent infections (within 130 days) among all newly diagnosed PLWH was only 2.73% in this area, which also deserves concern. The proportion of recent infections was lower than that in other areas with a high rate of HIV in China (40,41) and those in other countries (40,42), indicating that most of the newly diagnosed PLWH were not detected in time. HIV might be spread by many individuals unaware of their infection, leading to a widespread of HIV in this area.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, the conceptual analysis of this study made it possible to choose the viral load as the quantifiable variable par excellence of this study given its presence in several conceptual joints of viral transmission. It has also shown the involvement of the molecular components of HIV-1 on the residual risk in blood transfusion [20,21,22]. The serological markers (anti-HIV Ab, AgP24) identified as secondary variables to the concept by their presence throughout the infection would also contribute to the diagnosis of HIV-1 and the interpretation of recent or chronic infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…The 4% deltamethrin-impregnated collar is currently considered a tool for VL control. Some studies have indicated that its use in transmission areas reduces the prevalence of canine VL, but these studies have not shown its effects on the vector population ( Kazimoto 2016 , SevĂĄ et al 2016 ). This effect on the prevalence of canine VL is based on a reduction in blood feeding by the vector on dogs with collars, mediated by the repellent and insecticidal action of deltamethrin, a pyrethroid, impregnated in the collars ( Halbig et al 2000 , David et al 2001 , Maroli et al 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were reported by Kazimoto, who showed a 53% prevalence reduction with the use of these collars in a smaller number of dogs. In addition, a mathematical modelling study performed by SevĂĄ et al (2016) indicated that the use of insecticide-impregnated collars, when 90% coverage is achieved, can decrease the prevalence of seropositive dogs and incidence of human VL cases to zero.…”
mentioning
confidence: 99%